2013
DOI: 10.1115/1.4025557
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation of Pressure Drop in Expanding Microchannel Arrays

Abstract: The pressure effects of expanding the cross section of microchannels along the direction of flow are investigated across four rates of channel expansion in the flow boiling of R-134a. Prior investigation by the authors detailed the fabrication of four copper microchannel arrays and the pumped-loop apparatus developed to facilitate interchange of the microchannel specimens, allowing consistency across experiments. Significant beneficial pressure effects are observed to result from the expansion, including reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…A number of research efforts on flow boiling in microchannels were focused on understanding the underlying mechanisms [20,[42][43][44][45][46][47]. Recently, Kandlikar [48] provides excellent discussion on the effects of different forces acting on liquid-vapor interface and settles on the inertia, surface tension, shear, buoyancy, and evaporation momentum forces as the candidates for significance.…”
Section: Introductionmentioning
confidence: 97%
“…A number of research efforts on flow boiling in microchannels were focused on understanding the underlying mechanisms [20,[42][43][44][45][46][47]. Recently, Kandlikar [48] provides excellent discussion on the effects of different forces acting on liquid-vapor interface and settles on the inertia, surface tension, shear, buoyancy, and evaporation momentum forces as the candidates for significance.…”
Section: Introductionmentioning
confidence: 97%
“…Providing a variable (increasing) flow cross-sectional area along the flow length, a concept introduced by Mukherjee and Kandlikar [10,11], has garnered a lot of attention. Diverging channels [12,13], stepped microchannels [14,15] and expanding microchannels [16] have all been investigated with promising results. Kandlikar et al [17] presented an open microchannel manifold concept which provided high heat dissipation of over 500 W/cm 2 (5 MW/m 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of research efforts on flow boiling in microchannels were focused on understanding the underlying mechanisms [4][5][6][7][8][9][10][11][12][13]. Zhang et al [4] investigated the bubble nucleation, flow patterns, heat transfer and pressure performances in silicon microchannels by varying surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…He concluded that surface tension and evaporation momentum forces played a dominant role at microscale. Miner et al [12] experimentally investigated the pressure drop in an expanding microchannels array. They discussed the results in light of a comparative force analysis and linked the observed behaviors of the pressure drop and heat flux relationship with the balance of these forces.…”
Section: Introductionmentioning
confidence: 99%